2002
DOI: 10.1182/blood-2002-02-0494
|View full text |Cite
|
Sign up to set email alerts
|

Late complications following treatment for severe aplastic anemia (SAA) with high-dose cyclophosphamide (Cy): follow-up of a randomized trial

Abstract: High-dose cyclophosphamide (Cy) has been promoted as curative therapy for severe aplastic anemia (SAA). However, our randomized trial comparing antithymocyte globulin (ATG) and Cy was terminated early because of excess morbidity/ early mortality in the Cy arm. We now report analysis of secondary endpoints at a median of 38 months.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
31
0
1

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(32 citation statements)
references
References 14 publications
0
31
0
1
Order By: Relevance
“…1 Some might argue that treatment success in selected cases of syngeneic transplant is, in fact, not due to the transplant but is only the result of the immunosuppressive conditioning and posttransplant immunosuppression; as we know, treatment of AA with high-dose cyclophosphamide has been a topic of debate in the past. 17,18 Though the inability to measure donor chimerism precludes proof of syngeneic engraftment, rapid neutrophil recovery, as well as lack of influence of ATG, are strong surrogate indicators of actual engraftment rather than response to immunosuppressive treatment, which usually occurs after several months. 3 Despite the widespread use of ATG, its role in pre-transplant conditioning is also not clear in the setting of matched sibling transplant, where a randomized study failed to confirm the positive effect on engraftment observed in a retrospective comparison.…”
Section: Discussionmentioning
confidence: 99%
“…1 Some might argue that treatment success in selected cases of syngeneic transplant is, in fact, not due to the transplant but is only the result of the immunosuppressive conditioning and posttransplant immunosuppression; as we know, treatment of AA with high-dose cyclophosphamide has been a topic of debate in the past. 17,18 Though the inability to measure donor chimerism precludes proof of syngeneic engraftment, rapid neutrophil recovery, as well as lack of influence of ATG, are strong surrogate indicators of actual engraftment rather than response to immunosuppressive treatment, which usually occurs after several months. 3 Despite the widespread use of ATG, its role in pre-transplant conditioning is also not clear in the setting of matched sibling transplant, where a randomized study failed to confirm the positive effect on engraftment observed in a retrospective comparison.…”
Section: Discussionmentioning
confidence: 99%
“…81 However, cyclophosphamide was found to be excessively toxic because of fungal infections and deaths in a randomized study at NIH, and relapse and clonal evolution were observed. 82,83 Recently, long-term follow-up of SAA patients treated with high-dose cyclophosphamide showed that the cumulative incidence of invasive fungal infection was 21% in treatment-naive and 39% in refractory SAA. 84,85 These incidences of invasive fungal infections are higher than those observed with horse ATG and represent the major toxicity of the high-dose cyclophosphamide regimen.…”
Section: Immunosuppressive Therapymentioning
confidence: 99%
“…83,84 In contrast, an NIH randomized study was halted early due to the development of fungal infections and a much higher death rate in the cyclophosphamide arm, 85 and both relapse and cytogenetic evolution were observed. 86 The major toxicity of high-dose cyclophosphamide, prolonged neutropenia with concomitant susceptibility to infection, is now addressed by the Baltimore investigators by routine antimicrobial prophylaxis and prolonged G-CSF administration. Cyclophosphamide therapy does not eradicate PNH clones, and relapses now have been observed in Baltimore.…”
Section: Treatment Immunosuppressionmentioning
confidence: 99%